Monozygotic twins with 17q21.31 microdeletion syndrome - Vlckova, Marketa; Hancarova, Miroslava; Drabova, Jana; Slamova, Zuzana; Koudova, Monika; Alanova, Renata; Mannik, Katrin; Kurg, Ants; Sedlacek, Zdenek (Twin research and human genetics, 2014)
Chromosome 17q21.31 microdeletion syndrome is a genomic disorder caused by a recurrent 600 kb long deletion. The deletion affects the region of a common inversion present in about 20% of Europeans. The inversion is associated with the H2 haplotype carrying additional low-copy repeats susceptible to non-allelic homologous recombination, and this haplotype is prone to deletion. No instances of 17q21.31 deletions inherited from an affected parent have been reported, and the deletions always affected a parental chromosome with the H2 haplotype. The syndrome is characterized clinically by intellectual disability, hypotonia, friendly behavior and specific facial dysmorphism with long face, large tubular or pear-shaped nose and bulbous nasal tip. We present monozygotic twin sisters showing the typical clinical picture of the syndrome. The phenotype of the sisters was very similar, with a slightly more severe presentation in Twin B. The 17q21.31 microdeletion was confirmed in both patients but in neither of their parents. Potential copy number differences between the genomes of the twins were subsequently searched using high-resolution single nucleotide polymorphism (SNP) and comparative genome hybridisation (CGH) arrays. However, these analyses identified no additional aberrations or genomic differences that could potentially be responsible for the subtle phenotypic differences. These could possibly be related to the more severe perinatal history of Twin B, or to the variable expressivity of the disorder. In accord with the expectations, one of the parents (the mother) was shown to carry the H2 haplotype, and the maternal allele of chromosome 17q21.31 was missing in the twins.
Keywords: Polymorphism, Single Nucleotide; haplotypy; Chromosomes, Human, Pair 17; Humans; Twins, Monozygotic; lidské chromozomy, pár 17; jednonukleotidový polymorfismus; Female; dospělí; dvojčata monozygotní; Haplotypes; Smith-Magenis Syndrome; lidé; Smithův-Magenisův syndrom; mentální retardace; Adult; Intellectual Disability; ženské pohlaví; Male; chromozomální delece; Chromosome Deletion; mužské pohlaví